What presuppositions underlie studies on violence in Colombia? Between convictions and the daily reality of their choice (2010)
This article presents the results of an investigation into the presuppositions that guide studies on violence in Colombia. It identifies the “best thought convictions” of those who from different scientific disciplines evaluate study or try to understand